Developing building information models (BIM) for building handover, operation and maintenance. Issue 3 (26th June 2019) - Sadeghi, Marjan; Elliott, Jonathan Weston; Porro, Nick; Strong, Kelly
Abstract : Purpose: This paper aims to represent the results of a case study to establish a building information model (BIM)-enabled workflow to capture and retrieve facility information to deliver integrated handover deliverables. Design/methodology/approach: The Building Handover Information Model (BHIM) framework proposed herein is contextualized given the Construction Operation Information Exchange (COBie) and the level of development schema. The process uses Autodesk Revit as the primary BIM-authoring tool and Dynamo as an add-in for extending Revit's parametric functionality, BHIM validation, information retrieval and documentation in generating operation and maintenance (O&M) deliverables in the end-user requested format. Findings: Given the criticality of semantics for model elements in the BHIM and for appropriate interoperability in BIM collaboration, each discipline should establish model development and exchange protocols that define the elements, geometrical and non-geometrical information requirements and acceptable software applications early in the design phase. In this case study, five information categories (location, specifications, warranty, maintenance instructions and Construction Specifications Institute MasterFormat division) were identified as critical for model elements in the BHIM for handover purposes. Originality/value: Design- and construction-purposed BIM is a standard platform in collaborative architecture, engineering and construction practice, and the models are available for many recently constructed facilities. However, interoperability issues drastically restrict implementation of these models in building information handover and O&M. This study provides essential input regarding BIM exchange protocols and collaborative BIM libraries for handover purposes in collaborative BIM development.